Do Payment Technology Innovations Affect Currency Demand in Tunisia? - Mbazia, Nadia (International Journal of Economics and Financial Issues, 2023)
This study investigates the impact of non-cash payment technologies on demand for currency in Tunisia using the autoregressive distributed lag (ARDL) cointegration approach from 2010M12 to 2018M7. In this context, our findings indicate a negative influence of EFT-POS terminals on currency demand. We have also shown that the demand for currency is positively influenced by the increase in the number of ATMs and the volume of transactions made by bank cards in circulation, reflecting the frequent use of cards to receive cash in Tunisia. Whereas, the impact of increase in check payments on demand for currency is negative and not significant. The empirical evidence shows that there is preference for cash in payment habits by Tunisian consumers. So, it should be noted that despite the development of payment systems, cash still attractive and an easier substitute for non-cash payments in Tunisia.